1995
DOI: 10.1007/bf02246085
|View full text |Cite
|
Sign up to set email alerts
|

Bretazenil modulates sleep EEG and nocturnal hormone secretion in normal men

Abstract: Preclinical data suggest that the imidazodiazepinone derivative bretazenil (Ro 16-6028) has anxiolytic and anticonvulsant properties with only weak sedative effects. We examined the influence of oral administration of 1 mg bretazenil on the sleep EEG and the concomitant nocturnal secretion of cortisol, growth hormone and prolactin in ten healthy young men. After bretazenil we found a significant increase in stage 2 sleep and a significant reduction in stage 3 sleep. REM latency was prolonged. Spectral analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Diazepam 0.5 mg / kg decreased ACTH plasma levels after a single dose and decreased ACTH and corticosterone after repeated administration in the rat (Bruni et al 1980). During sleep, orally administered bretazenil (1 mg) in men decreased cortisol secretion (Guldner et al 1995). Our Þnding of a blunting of ACTH is compatible with an NMDA-antagonistic and a GABA A -agonistic e¤ect of Mg 2+ .…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Diazepam 0.5 mg / kg decreased ACTH plasma levels after a single dose and decreased ACTH and corticosterone after repeated administration in the rat (Bruni et al 1980). During sleep, orally administered bretazenil (1 mg) in men decreased cortisol secretion (Guldner et al 1995). Our Þnding of a blunting of ACTH is compatible with an NMDA-antagonistic and a GABA A -agonistic e¤ect of Mg 2+ .…”
Section: Discussionmentioning
confidence: 58%
“…A detailed description of the conventional sleep analysis and the methodology of the spectral analysis is described elsewhere (Guldner et al 1995).…”
Section: Sleep-eeg Analysismentioning
confidence: 99%
“…The development of some compounds, such as the benzodiazepine receptor partial agonist bretazenil (a benzodiazepine derivative) 45,46 and the GABA A receptor α2 and α3 subunit agonist SL651498 (REF. 47), was discontinued owing to unexpected sedative and/or amnestic effects.…”
Section: Gaba–benzodiazepine Systemmentioning
confidence: 99%
“…Although the data are inconsistent, benzodiazepine hypnotics seem to affect hormonal secretions. Various studies have found a suppression of cortisol or, less desirable, of GH and a stimulation of prolactin (4,12,27).…”
mentioning
confidence: 99%